Host tree preference of vascular epiphytes and climbers in a subtropical montane cloud forest of northwest Argentina - Malizia, Agustina (2003)
In a Neotropical montane environment of NW Argentina (22º S , 1800 m elevation) vascular epiphyte and climber communities were described in one ha of forest in order to assess the relationships between epiphyte and climber community composition and host tree species, and to infer associations between epiphyte and climber and tree morphological-functional groups. The six most abundant tree species were significantly segregated along the first and second axes of a non metric multidimensional scaling ordination based on their epiphyte and climber species composition and coverage. On the first axis tree species discriminated according to foliar phenology and bole heights. These factor likely create a dry and well-lit microenvironment within the canopy. The most abundant climber (Macfadyena unguis-cati) was strongly associated with trees with apparently drier and brighter microenvironments while at least eight epiphyte and climber species were associated with trees with more humid and darker microenvironments. Along the second ordination axis tree species were segregated according to tree and crown diameter, total tree and bole height, and bark type. Taller tree species with rough bark, larger diameters and crown dimensions dominated one end of the second axis in associations with at least eleven epiphyte and climber species. Overall, epiphyte and climber community composition differed among host tree species and may be explained in part by measurable host tree characteristics.